8.3k views
4 votes
Sigma F = T-10m but a = 0 in the equation sigma F = ma

Sigma F = T-10m but a = 0 in the equation sigma F = ma-example-1
User Bendecko
by
5.7k points

1 Answer

5 votes

Answer:

m = T/10 = (1/10) T

Step-by-step explanation:

From the question given:

∑F = ma .... (1)

∑F = T – 10m .... (2)

a = 0 m/s²

m =?

Thus, we can obtain m in terms of T as shown below:

From equation (1)

∑F = ma

a = 0 m/s²

∑F = ma = m × 0

∑F = 0

Next, substitute the value of ∑F into equation (2) to obtain m. This is illustrated below:

∑F = T – 10m

∑F = 0

0 = T – 10m

Rearrange

0 + 10m = T

10m = T

Divide both side by 10

m = T/10

m = (1/10) T

Therefore, m is (1/10) T

User Vicentazo
by
6.2k points